2020
DOI: 10.5614/j.eng.technol.sci.2020.52.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surface Characteristics of Medical-grade 316L Stainless Steel Processed by Sand-blasting, Slag Ball-blasting and Shot-blasting Treatments

Abstract: All blasting treatments with various blasting particles increased the roughness and hardness of the steel surface.  The roughest stainless steel surface was achieved by the slag ball-blasting treatment, but shot-blasting produced the stainless steel with the hardest surface and the thickest hard subsurface layer.  The physical properties and surface morphology of the particles or shot used in the blasting treatment are critical parameters in determining the surface characteristics of blasted stainless steel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…4). Similarly, Arifvianto et al [34] indicated an increased Si component in the surface layer coming from the shots material.…”
Section: Surface Hardnessmentioning
confidence: 87%
See 1 more Smart Citation
“…4). Similarly, Arifvianto et al [34] indicated an increased Si component in the surface layer coming from the shots material.…”
Section: Surface Hardnessmentioning
confidence: 87%
“…The increase in surface hardness can be attributed to the small fragments of shots' particles that are formed when they strike the surface of the sample. During a strike, the high kinetic energy of the particles can break these materials into many small fragments [34]. Such small fragments, which are irregularly shaped, are then deposited on the surface by successive impacts of the ceramic medium, leading to a significant local increase in hardness.…”
Section: Surface Hardnessmentioning
confidence: 99%
“…Many scientific works have been devoted to the solution of such problems, which are aimed both at the description of impact contact with an obstacle of an individual particle [1][2][3][4][5][6][7][8][9], and the mass jet stream of particles with access to hardening of the surface layer [10,11], cleaning surfaces [12][13][14] destruction of the surface layer [15,16] and optimization of various technological processes [17,18].…”
Section: Introductionmentioning
confidence: 99%